Increasing of Reproduction Efficiency of Cattle Through the Application of Synchronization Technology - Herdis .; Maman Surachman; Ida Kusuma; Epih R Suhana (Indonesian Center for Animal Research and Development, 1999)
The constraint of cattle development in Indonesia is low productivity, which was caused by low reproduction efficiency. Unestroes and difficulty of heat detection influenced to the calving interval. This calving interval is one of the causal factors of low reproduction efficiency. The efforts to solve this problem are to control and to predict heat period using synchronization technology. Synchronization technology on catlle has been developed from corpus luteum enucleated, utilizing of gonadotropin, progesteron, estrogen, prostaglandine and modification of those hormones. Application method for synchronization could be done by intra musculair, subcutan implantation, intra vaginal and mixed with food. Each method has its own strength and weaknesses. However, to handle anestroes cases is more effective to use combination of progesteron, PGF2α and estrogen. In order to obtain reproduction efficiency it is suggested to take the anestroes in hand as soon as possible. Key words : Cattle, synchronization estrous